2017
DOI: 10.1080/2162402x.2017.1286437
|View full text |Cite
|
Sign up to set email alerts
|

Composite biomarkers defined by multiparametric immunofluorescence analysis identify ALK-positive adenocarcinoma as a potential target for immunotherapy

Abstract: Anaplastic lymphoma kinase (ALK) inhibitors have been successfully developed for non-small cell lung carcinoma (NSCLC) displaying chromosomal rearrangements of the ALK gene, but unfortunately resistance invariably occurs. Blockade of the PD-1-PD-L1/2 inhibitory pathway constitutes a breakthrough for the treatment of NSCLC. CD8C T cells was also observed in ALK-positive lung cancer patients compared with EGFR-mutated (p D 0.03) or WT patients (p D 0.012). These results strongly suggest that a subgroup of ALK-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…It can semi quantitatively assess the mRNA signal in target cells with conventional light microscopy [ 88 ]. Finally, multiplex IHC analyses are also being developed to analyze in parallel the ALK status and the expression of certain checkpoint inhibitors, and these analyses can participate in studies into novel therapeutic strategies [ 89 ].…”
Section: Methods For Detection Of An Alk Rearramentioning
confidence: 99%
“…It can semi quantitatively assess the mRNA signal in target cells with conventional light microscopy [ 88 ]. Finally, multiplex IHC analyses are also being developed to analyze in parallel the ALK status and the expression of certain checkpoint inhibitors, and these analyses can participate in studies into novel therapeutic strategies [ 89 ].…”
Section: Methods For Detection Of An Alk Rearramentioning
confidence: 99%
“…64 which cells are targeted by antagonists of inhibitory receptors CD8 + T cells The current dogma supported by various preclinical and clinical data argues in favour of a major role of T cells and especially CD8 + T cells to explain the therapeutic activity of antagonists of inhibitory receptors (figure 2). 65 66 The presence of pre-existing T cells before therapy correlated with the clinical activity of PD-1 and CTLA-4 blockade, as TIL density in melanoma patients treated by anti-CTLA-4 correlated with good clinical response. 67 Another study reported that pre-existing CD8 + T cells at the invasive tumour margin were a prerequisite for the efficacy of PD-1 blockade in a cohort of 15 patients treated for melanoma.…”
Section: Blockade Of Intrinsic Tumour Signalling Mediated By Pd-l1mentioning
confidence: 99%
“…A multi-parametric immunofluorescence study including ALK, CD8, PD-1 and PD-L1 was recently performed. In comparison to EGFR-mutated or WT lung adenocarcinomas, ALK-positive tumors had a higher expression of PD-L1 and a higher number of intra-tumoral CD8+ T cells orPD-1+CD8+Tcells [19].…”
Section: Discussionmentioning
confidence: 89%